Efektivitas Tata Kelola Keuangan di Sekolah Kerajaan Thailand: Studi Kasus Sekolah ISO - Lailatus Sa’diyah; Erna Resmiatini (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study has one main objective: to analyze the effectiveness of financial management at Rongrian Ban ISO School (ISO), one of the royal schools in Thailand. The research method used a qualitative approach with a case study. Data collection techniques were conducted through interviews, observation, and documentation. The results of the study indicate that financial management at ISO School has been carried out in a planned, transparent, and accountable manner. Through this study, it was discovered that the budget planning process was compiled based on the School Development Plan (RPS) and monitored through internal and external audits. Budget implementation was adjusted to educational needs while still considering efficiency and effectiveness. Despite facing obstacles such as budget limitations and policy changes, the school was able to overcome them through adaptive strategies. From this study, it can be concluded that financial governance at ISO School can be a reference model for increasing transparency and accountability in the management of educational funds.